Acute myocarditis mimicking ST – elevation myocardial infarction in a young adult with pharyngitis – a case report - Christou, Andreas; Kaperonis, Alexandros; Veskoukis, Nikolaos (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Acute myocarditis (AM) is a life-threatening inflammatory disease that manifests with a highly variable range of clinical symptoms, sometimes mimicking those of myocardial infarction. The aim of this report was to describe the diagnostic challenges of AM. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 22-years old male previously diagnosed with pharyngitis arrived in the emergency room (ER) with retrosternal chest pain. The electrocardiogram (ECG) showed ST elevation in inferior and posterior leads and reciprocal changes with ST depression in anterolateral leads. Laboratory tests revealed elevated cardiac enzymes and bedside echocardiogram (ECHO) revealed hypokinesis of the inferior wall. Initial diagnosis of ST elevation myocardial infarction (STEMI) was made. Coronary angiogram showed normal epicardial coronary arteries and cardiac magnetic resonance imaging (CMRI) revealed subepicardial late gadolinium enhancement (LGE). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. This case was proven challenging due to the unusual ECG and ECHO findings, mimicking inferoposterior STEMI. The need for available angiography and CMRI was mandatory for the final diagnosis of AM.